Excellent reliability for MRI grading and prognostic parameters in acute hamstring injuries. Issue 18 (13th September 2013) - Hamilton, B; Whiteley, R; Almusa, E; Roger, B; Geertsema, C; Tol, Johannes L
Abstract : Background: Categorical grading and other measurable MRI parameters are frequently utilised for predicting the outcome of hamstring injuries. However, the reliability and smallest detectable difference (SDD) have not been previously evaluated. It therefore remains unclear if the variability in previously reported results reflects reporting variation or actual injury status. Methods: 25 hamstring injuries were scored by two experienced radiologists using the Peetrons grading and specific prognostic MRI parameters: distance from ischial tuberosity (cm), extent (cranio to caudal, anterior to posterior, medial to lateral; (cm)), maximum cross-sectional area (%), volume (cm 3 ) of the oedema. The interobserver and intraobserver reliability was calculated along with the SDDs for each scale variable. Results: There were 3 Grade 0 (12%), 11 grade 1 (44%), 9 grade 2 (36%) and 2 grade 3 (8%) injuries. Cronbach's α values for grading were 1.00 (inter) and 0.96 (intra), respectively. The intraclass correlation coefficients for the prognostic MRI parameters were between 0.77 and 1.0. The SDDs varied between each parameter. Conclusions: Excellent interobserver and intraobserver reliability was found for grading and prognostic MRI parameters in acute hamstring injuries. In daily practice and research, we can be confident that scoring hamstring injuries by experienced radiologists is reproducible. The documented SDDs allow meaningful clinical inferences to be made when assessing observed and reported changes in MRI status.